2019
DOI: 10.1097/jsm.0000000000000786
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Treatment Comparisons for Large and Massive Rotator Cuff Tears: A Network Meta-analysis

Abstract: Background: There is no consensus about the best choice between all the options available for large and massive rotator cuff tear (mRCTs) management. Objective: To determine the comparative effectiveness of current treatment options for management of large and mRCTs. Design: Network meta-analysis. Setting: We searched the Cochrane systematic reviews, MEDLINE and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
0
9
0
2
Order By: Relevance
“…Entretanto, este estudo inclui tanto pacientes com roturas irreparáveis como aqueles com artropatia do manguito rotador, além de utilizar uma amostra de pacientes com idade mais avançada. Maillot et al, 8 em uma metanálise envolvendo 20 estudos e 1.233 pacientes, compararam as diferentes formas de tratamento para as roturas grandes ou extensas do manguito rotador (tratamento conservador, desbridamento, reparo parcial, reparo completo, transferência do grande dorsal, uso de "patches", plasma rico em plaquetas e artroplastia reversa). Observaram que o único tratamento que demonstrou superioridade frente aos demais foi a transferência do grande dorsal.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Entretanto, este estudo inclui tanto pacientes com roturas irreparáveis como aqueles com artropatia do manguito rotador, além de utilizar uma amostra de pacientes com idade mais avançada. Maillot et al, 8 em uma metanálise envolvendo 20 estudos e 1.233 pacientes, compararam as diferentes formas de tratamento para as roturas grandes ou extensas do manguito rotador (tratamento conservador, desbridamento, reparo parcial, reparo completo, transferência do grande dorsal, uso de "patches", plasma rico em plaquetas e artroplastia reversa). Observaram que o único tratamento que demonstrou superioridade frente aos demais foi a transferência do grande dorsal.…”
Section: Discussionunclassified
“…However, this review included patients with irreparable tears and rotator cuff arthropathy, who were also older when compared to our subjects. Maillot et al, 8 in a meta-analysis involving 20 studies and 1,233 patients, compared different forms of treatment for large or extensive rotator cuff tears (conservative treatment, debridement, partial repair, complete repair, latissimus dorsi transfer, patches, platelet-rich plasma, and reverse arthroplasty). Latissimus dorsi transfer was the only treatment showing superiority over the others.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent systematic review identified that 42% of RCT can be classified as irreparable tears 5 . Although various surgical techniques have been developed and applied, postoperative complications and uncertain outcomes often trouble both clinicians and patients 6 . Galatz et al 7 report that the re-tear rate of massive irreparable RCT could be up to 94%.…”
Section: Introductionmentioning
confidence: 99%